Development of a model of brain function change based on treatment of heterogeneous hemispheres on the depression of addicts - Malekzadeh, Setareh; Ahadi, Hassan; Dortaj, Fariborz (Researcher Bulletin of Medical Sciences, 2022)
Objective: The aim of this istudy is to determine the model of brain function change based on treatment of heterogeneous hemispheres on the depression of addicts. Materials and Methods: This research is a quasi-experimental study with a pre-test-post-test design with a control group, which 20 male addicts leaving in the city of Karaj, Iran. Beck Depression Inventory and Blood Test was used. We selected 20 out of 100 people at random and placed them in two experimental and control groups equally (10 experimental group and 10 control group). Evaluation of the subjects by the Depression Inventory and blood test before training and after training of the experimental group. The subjects in the experimental group were trained for 16 sessions 2 days a week, two hours a day, and the control group did not receive any intervention. The obtained data were analyzed using ANKOA statistical method and research data was analyzed with SPSS software version 22. Results: the reuslts showed that the subjects in the experimental group after training were significantly different from the control group in their scores of depression and increase in chemical carriers (serotonin and dopamine). In other words, brain change model based on heterogeneous hemisphere treatment was effective on depression of withdrawal addicts with 95% probability. Conclusion: Teaching a model of brain function change based on heterogeneous hematopoietic treatment was effective on depression in withdrawal addicts. approved.